Following Darwin's footsteps: evaluating the impact of an activity designed for elementary school students to link historically important evolution key concepts on their understanding of natural selection - Sá-Pinto, Xana (2022)
While several researchers have suggested that evolution should be explored from the initial years of schooling, little information is available on effective resources to enhance elementary school students' level of understanding of evolution by natural selection (LUENS). For the present study, we designed, implemented, and evaluated an educational activity planned for fourth graders (9 to 10 years old) to explore concepts and conceptual fields that were historically important for the discovery of natural selection. Observation field notes and students' productions were used to analyze how the students explored the proposed activity. Additionally, an evaluation framework consisting of a test, the evaluation criteria, and the scoring process was applied in two fourth-grade classes (N = 44) to estimate elementary school students' LUENS before and after engaging in the activity. Our results show that our activity allowed students to link the key concepts, resulting in a significant increase of their understanding of natural selection. They also reveal that additional activities and minor fine-tuning of the present activity are required to further support students' learning about the concept of differential reproduction.